2015
DOI: 10.1017/s0022215115000341
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral agents convey added benefit over steroids alone in Bell's palsy; decompression should be considered in patients who are not recovering

Abstract: Combination therapy including antiviral medication significantly improves outcomes in patients with severe Bell's palsy. Decompression should be considered in patients who have not recovered with drug treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 93 publications
(243 reference statements)
0
2
0
Order By: Relevance
“…During the diagnostic process, a comprehensive history and physical examination aim to exclude neurological, otorhinolaryngological, infectious and inflammatory or neoplastic factors, as well as cerebellopontine angle pathology or vascular insufficiency. The House Brackmann grading system is useful for evaluating changes in nerve function [4][5][6]. The estimated incidence of Bell's palsy is 10-40 per 100,000 people.…”
Section: Introductionmentioning
confidence: 99%
“…During the diagnostic process, a comprehensive history and physical examination aim to exclude neurological, otorhinolaryngological, infectious and inflammatory or neoplastic factors, as well as cerebellopontine angle pathology or vascular insufficiency. The House Brackmann grading system is useful for evaluating changes in nerve function [4][5][6]. The estimated incidence of Bell's palsy is 10-40 per 100,000 people.…”
Section: Introductionmentioning
confidence: 99%
“…The widely quoted Scottish Bell's Palsy Study 1 confirmed the efficacy of prednisolone in the recovery of facial function, but suggested that the antiviral acyclovir provided no benefit, whether administered alone or in combination with prednisolone. An article in this issue by de Ru and colleagues 2 critically reviews the evidence on this topic by both examining the literature and considering new evidence 3 . They suggest that antiviral medication can be crucial when given in the most severe cases, which include those with severe deficit and the elderly.…”
mentioning
confidence: 99%